"Die at home": a contextualization and mapping of the New York City Draft Riots of 1863 - Hoehne, Patrick Tyler, author; Gudmestad, Robert, advisor; Leisz, Stephen, committee member; Payne, Sarah, committee member (Colorado State University. Libraries, 2018)
This thesis attempts to contextualize and explore the New York City Draft Riots of 1863 – one of the deadliest instances of civil insurrection in American history – in order to prove that the violence of the riots was neither completely undirected nor uniform. At the heart of this argument is the simple idea that violence is never random. The first two chapters contextualize the Draft Riots within the greater experience of New York's Irish population, both in the Civil War and at home in New York City. The final two chapters, through a spatiotemporal analysis, seek to isolate patterns within riot violence in order to better understand the differing targets and tactics of rioters throughout the unrest.